Castleman's disease in an adolescent - Ujjwala Singh; Manish S Nayak; Shreya Singh; K Rajgopal Shenoy (Apollo Medicine)
Castleman’s disease is a clinic-pathological entity of unknown etiology with non–neoplastic lymph node hyperplasia. It is extremely rare and can be found in patients of all age groups. It can present as localized with local signs and symptoms or disseminated disease which includes a wide range of systemic problems. Our patient is a 15-year-old adolescent female with nonspecific features of abdominal pain, vomiting. Blood and Imaging studies were inconclusive and the diagnosis of Castleman’s diseases was confirmed by histopathology. Here, we discuss the importance of considering Castleman’s diseases as a differential diagnosis for a case of acute abdomen.